HUMAN–AI COLLABORATION AS A NEW DETERMINANT OF GENERATION Z WORK PRODUCTIVITY IN THE ERA OF DIGITAL TRANSFORMATION: A SYSTEMATIC LITERATURE REVIEW (POLITEKNIK LP3I JAKARTA, 2026)
Digital transformation has fundamentally reshaped Human Resource Management (HRM) through the integration of Artificial Intelligence (AI) into organizational processes. Rather than functioning solely as a technology that replaces human labor, AI is increasingly recognized as an intelligent partner that augments human capabilities through the concept of Human–AI Collaboration. Recent developments have extended AI applications beyond process automation to include Human Capital Management, talent management, digital decision-making, competency development, and Digital Human Resource Management (Digital HRM). These developments are particularly relevant to Generation Z, a digitally native workforce characterized by high technological adaptability and readiness to collaborate with AI-enabled systems. This study aims to examine Human–AI Collaboration as a new determinant of Generation Z's work productivity using a Systematic Literature Review (SLR) approach. The review synthesized six primary empirical studies published between 2021 and 2025 through systematic stages of identification, screening, quality assessment, data extraction, and thematic synthesis. To strengthen the conceptual interpretation, two complementary empirical studies and several internationally recognized theoretical references were incorporated into the discussion. The findings indicate that AI enhances work productivity by automating routine tasks, improving data-driven decision-making, strengthening digital competencies, supporting Human Capital Management, optimizing talent management practices, and enabling Digital HRM. The review further demonstrates that the effectiveness of Human–AI Collaboration depends on organizational readiness, digital competence, innovation culture, Human Resource Information Systems (HRIS), and digital transformation strategies. Moreover, the synthesis of empirical evidence and theoretical perspectives suggests that organizational productivity is increasingly generated through complementary collaboration between human intelligence and artificial intelligence rather than technological substitution. Despite the growing body of literature, empirical research examining Human–AI Collaboration as a determinant of Generation Z's work productivity remains limited, particularly in the Indonesian context. This study therefore proposes a conceptual framework positioning Human–AI Collaboration as a strategic mechanism linking AI adoption, digital transformation, and workforce capabilities to sustainable work productivity in the era of digital transformation.